Socialization and Counseling to Enhance Teenagers' Understanding of the Dangers of Addictive Substances for Students of Harapan Tiga Private High School - Aritonang, Barita; Syarifuddin, Shofian; Sitepu, Rahmadani; Meilani, Debi (JURNAL PENGMAS KESTRA (JPK), 2024)
Community Service aims to enhance students' understanding of Harapan Tiga Private High School's dangers of addictive substances and their impact on physical and mental health. Additionally, community service strives to encourage positive attitudes and behaviors so that students can face pressures and temptations without resorting to addictive substances. Adolescence is a critical period where teenagers undergo various developmental tasks and social pressures, including the risk of drug abuse. Through a comprehensive program of socialization and counseling, students are provided with information about types of addictive substances, their negative impacts, and strategies to combat peer pressure. The implementation method involves a collaborative approach with the school, preparation stages, activity planning, and partner participation. The results of these activities show an increase in students' understanding of the dangers of addictive substances, positive attitude changes, and the establishment of cooperation between the school, parents, and the community in preventing drug abuse among teenagers. Teaching knowledge about addictive substances and their misuse from an early age, through both formal and informal education, plays an important role in shaping teenagers' understanding of the dangers of addictive substances. By increasing understanding and awareness among teenagers, it is expected that the risk of drug abuse will decrease and their quality of life will improve. In conclusion, the results of community service show a significant increase in students' understanding of the dangers of addictive substances and the formation of positive attitudes, thereby preventing drug abuse among teenagers.